1983
DOI: 10.1002/pssa.2210760211
|View full text |Cite
|
Sign up to set email alerts
|

Radiation damage in ion-implanted quartz crystals. II. Annealing behaviour

Abstract: BYQuartz crystals (Z-cuts) are implanted with Ar+ (150 keV) and He+ (35 keV) ions a t room temperature. The annealing behaviour of the radiation damage between 300 and 1370 K is investigated by Rutherford backscattering spectrometry (RBS). Three stages with different thermal stability of the defects are found: 1. Simple defects produced a t nuclear deposited energy densities Q, 5 1 x 1020 keV cm-S can be completely annealed a t 770 K. 2. Amorphized microregions generated between Q, = 1 x 10eo keV om-3 and 2.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
2

Year Published

1983
1983
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 8 publications
1
9
0
2
Order By: Relevance
“…On the other hand, the rearrangement of the structure into a periodic network ͑crystallization͒ would require a high degree of mobility of the ͓SiO 4 ͔ tetrahedra, which is absent in pure silica and prevents epitaxial crystallization of SiO 2 . [12][13][14] Nevertheless, Devaud et al 15 found that annealing in air of ''self-ion'' (Si ϩ ϩ2O ϩ ) implanted natural Brazilian quartz samples leads to epitaxial recrystallization of the amorphous layers at 1050°C. 9 The recovery of crystallinity, instead, is favored in underconnected networks, i.e., those having an excess of structural freedom ( f Ͼ0), which only rarely retain an aperiodic structure but show the tendency to recrystallize even at low temperatures and at low activation energies.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the rearrangement of the structure into a periodic network ͑crystallization͒ would require a high degree of mobility of the ͓SiO 4 ͔ tetrahedra, which is absent in pure silica and prevents epitaxial crystallization of SiO 2 . [12][13][14] Nevertheless, Devaud et al 15 found that annealing in air of ''self-ion'' (Si ϩ ϩ2O ϩ ) implanted natural Brazilian quartz samples leads to epitaxial recrystallization of the amorphous layers at 1050°C. 9 The recovery of crystallinity, instead, is favored in underconnected networks, i.e., those having an excess of structural freedom ( f Ͼ0), which only rarely retain an aperiodic structure but show the tendency to recrystallize even at low temperatures and at low activation energies.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] In order to control the optical and electrical properties of ␣-quartz by ion implantation, a good knowledge of the thermal stability of the radiation-induced defects and the disordered phase is required, and effective procedures for defect recovery and recrystallization need to be developed. [16][17][18] Moreover, SPEG of amorphous layers in ␣-quartz upon thermal annealing was, up to now, ruled out, both from experimental results 19 and theoretical considerations. 14 In silicon, SPEG has been found to take place at rather low temperatures (450-550°C) with an activation energy of 2.7 eV.…”
mentioning
confidence: 99%
“…For comparison with other ion irradiation studies, note that Fischer et al [1983b] found that a quasi -random arrangement of both when it was used in the construction of apparatus for irradiation, Thompson [1957] tested vitreous Si02 rods in 3-point bending tests at 77 K. Specimens…”
Section: Amorphization Wittels and Sherrillmentioning
confidence: 99%